2021
DOI: 10.3389/fphar.2020.603235
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Nanoparticle Enhances the Anticancer Effect of Cisplatin by Inhibiting PI3K/AKT and JAK/STAT3 Pathway in Rat Ovarian Carcinoma Induced by DMBA

Abstract: Cisplatin has been used for decades for the treatment of ovarian cancer. However, despite its potent anticancer effect, cisplatin’s efficacy as a single agent was inadequate in patients with advanced stage. Curcumin has been shown to sensitize cisplatin activity in several cancer models. However, the low bioavailability of curcumin has limited its anticancer potential. Hence, nano-formulation of curcumin was developed to increase its therapeutic efficacy in ovarian cancer. The objective of this study was to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…Cur can increase the generation of ROS, which leads to many dysfunctions in cells, including DNA damage, cell apoptosis, and cell cycle arrest in CRC [ 15 , 16 , 17 ]. Cur also exhibits an antitumor effect as an inhibitor of the transcription factor signal transducer and activator of transcription 3 (STAT3) in various tumors [ 18 , 19 , 20 , 21 ], and STAT3 is reported to upregulate the expression of NNMT in CRC [ 22 ]. In addition, it has been reported that Cur potentiates the effect of many chemotherapy drugs, including 5-FU [ 18 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cur can increase the generation of ROS, which leads to many dysfunctions in cells, including DNA damage, cell apoptosis, and cell cycle arrest in CRC [ 15 , 16 , 17 ]. Cur also exhibits an antitumor effect as an inhibitor of the transcription factor signal transducer and activator of transcription 3 (STAT3) in various tumors [ 18 , 19 , 20 , 21 ], and STAT3 is reported to upregulate the expression of NNMT in CRC [ 22 ]. In addition, it has been reported that Cur potentiates the effect of many chemotherapy drugs, including 5-FU [ 18 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cur also exhibits an antitumor effect as an inhibitor of the transcription factor signal transducer and activator of transcription 3 (STAT3) in various tumors [ 18 , 19 , 20 , 21 ], and STAT3 is reported to upregulate the expression of NNMT in CRC [ 22 ]. In addition, it has been reported that Cur potentiates the effect of many chemotherapy drugs, including 5-FU [ 18 , 23 , 24 ]. It has been observed that, regardless of the drug that it is combined with, Cur always results in an enhanced effect with reduced dose and side effects [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin is a natural polyphenol compound derived from turmeric, and commonly used as a natural colorant [ 1 ]. Compared with artificial synthetic food additives, curcumin is nontoxic [ 2 ] and has anti-inflammatory [ 3 ], antibacterial [ 4 ], anti-cancer [ 5 ], and antioxidant [ 6 ] effects. However, curcumin has poor water solubility, low bioavailability and tends to degrade at neutral and basic conditions, limiting its use in functional foods.…”
Section: Introductionmentioning
confidence: 99%
“…Combination treatment of curcumin and cisplatin managed to inhibit phosphorylation of JAK and STAT3 in ovarian and papillary thyroid cancer cells leading to enhanced proliferation and reduced stemness of potential cancer stem cells ( Khan AQ. et al, 2020 ; Sandhiutami et al, 2021 ). In osteosarcoma cells, curcumin inhibited the p -JAK2/p-STAT3 pathway which was involved in lung metastasis whereas in lung cancer, curcumin suppressed activation of p-STAT3 both in vitro and in vivo ( Alexandrow et al, 2012 ; Sun et al, 2019 ).…”
Section: Receptor Tyrosine Kinase Signaling Pathways Targeted By Curcumin In Cancermentioning
confidence: 97%